Comparative analysis of conventional and bifaical solar cells under various illumination conditions - Aliev, R.; Komilov, M.; Aliev, S.; Gulomova, I. (Physics and Chemistry of Solid State, 2024)
In this work, through a detailed analysis of the mechanisms of photon absorption, photogeneration processes and the efficiency of nonequilibrium charge carriers’ collection under conditions of rear and double-sided illumination, the initial physical parameters of the internal layers and the design of double-sided sensitive solar cells with n+-p junction on the front side has been studied. The modern numerical simulation method was used to study the solar cells. Models of silicon solar cells (SC) contains p+-p-n+ structure with separating n+-p-junction near the frontal (upper) surface. Increasing the doping concentration in the p-region notably enhances the steepness of the I-V curve, indicative of improved quality of the solar cell and p-n junction. Specifically, an optimal doping concentration of 1015 cm⁻³ yields the highest efficiency, demonstrating the critical role of doping concentration in performance optimization. Furthermore, variations in doping concentration exert differential impacts on key parameters. Notably, open-circuit voltage, fill factor, efficiency, maximum output power, and serial resistivity exhibit distinct responses to changes in doping concentration. For instance, an increase in doping concentration from 1013 cm⁻³ to 1015 cm⁻³ results in notable improvements across these parameters, highlighting the significance of precise doping control in enhancing solar cell performance. When, photoelectric parameters of conventional and double side sensitive solar cells are compared, it has been found that the short circuit current and open circuit voltage of double side solar cell are 2 times and 18 mv greater than those of conventional solar cell.